Ferroelectric Polarization Switching Behavior of Hf0.5Zr0.5O2 Gate Dielectrics on Gallium Nitride High‐Electron‐Mobility‐Transistor Heterostructures. Issue 7 (20th November 2019) - Wu, Chunlei; Ye, Hansheng; Grisafe, Benjamin; Datta, Suman; Fay, Patrick
Abstract : Ferroelectric (FE) materials have strong polarization effects and are switchable by the applied electric field, making them attractive candidates for polarization engineering in GaN‐based devices. Herein, the FE response of Hf0.5 Zr0.5 O2 (HZO) deposited by atomic layer deposition (ALD) on AlGaN/GaN high‐electron‐mobility transistor (HEMT) heterostructures is characterized and analyzed in both metal–ferroelectric–semiconductor (MFS) and metal–ferroelectric–oxide–semiconductor (MFOS) configurations. Strong 2D‐electron gas (2DEG) channel modulation from FE polarization switching is observed. Significant FE polarization switching as well as distinct polarization recovery behavior is observed for the first time in GaN transistor structures. The polarization recovery appears to be related to the presence of significant coupling between the FE layer and the 2DEG channel at the AlGaN/GaN heterointerface. These results have significant implications for the design of devices exploiting FE effects in GaN and related materials. Abstract : Herein, the ferroelectric (FE) polarization switching behavior of Hf0.5 Zr0.5 O2 (HZO) on AlGaN/GaN high‐electron‐mobility transistor (HEMT) heterostructures is experimentally studied. Significant FE polarization switching as well as distinct polarization recovery behavior is observed and analyzed. These results have significant implications for device designs exploiting FE effects in GaN and related materials.